Implementasi Maqashid Syariah dan Aktualisasinya dalam Pengembangan Sistem Ekonomi Islam - Ahmad Mukri Aji; Syarifah Gustiawati Mukri (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
The implementation of maqashid sharia as the basic theory of Islamic justice and welfare is a determining factor in the development of an increasingly growing Islamic economic system. The development of an increasingly complex Islamic economic system opens up opportunities for ijtihad to create new norms for banking products and other sharia transactions. Sharia economists and banking practitioners not only master the science of muamalah fiqh and its applications, but also must understand the maqashid sharia as the goal of establishing Islamic law. The method used in this study is a qualitative method with a literature approach. The results of the study state that the actualization of the maqashid sharia concept in product development and sharia transactions can be applied to modern transactions such as interbank money market instruments, sukuk schemes, repos, syndicated financing between sharia banks or conventionally, restructuring, property indent financing, ijarah maushufah fiz zimmah, hybrid take over and refinancing, forfeiting, overseas financing, KTA scheme, multipurpose financing, credit card design, laws related to fiduciary guarantees, mortgages, and mortgages, maqashid of annuities, Tawarruq, net revenue sharing, installments gold, gold investment, as well as a number of new cases that continue to emerge that require solution and innovative arguments in the formation of new norms in modern life transactions.Keywords: Implementation; Maqashid Shari'ah; Islamic economics Abstrak Implementasi maqashid syariah sebagai teori dasar keadilan dan kesejahteraan Islam merupakan faktor penentu dalam pengembangan sistem ekonomi Islam yang semakin berkembang. Perkembangan sistem ekonomi Islam yang semakin kompleks, membuka peluang ijtihad terhadap penciptaan norma baru terhadap produk perbankan dan transaksi syari’ah lainnya. Para Ekonom syariah dan praktisi perbankan tidak hanya sekedar menguasai ilmu fikih muamalah dan aplikasinya saja, tetapi juga harus memahami maqashid syariah sebagai tujuan ditetapkannya hukum Islam. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan pendekatan literatur. Hasil penelitian menyatakan bahwa aktualisasi konsep maqashid syariah dalam pengembangan produk dan transaksi syari’ah dapat diterapkan pada transaksi modern seperti instrumen money market inter bank, skim-skim sukuk, repo, pembiayaan sindikasi antar bank syariah atau dengan konvensional, restrukturisasi, pembiayaan property indent, ijarah maushufah fiz zimmah, hybrid take over dan refinancing, forfeiting, overseas financing, skim KTA, pembiayaan multiguna, desain kartu kredit, hukum-hukum terkait jaminan fiducia, hypoteik, dan hak tanggungan, maqashid dari anuitas, tawarruq, net revenue sharing, cicilan emas, investasi emas, serta sejumlah kasus-kasus baru yang terus bermunculan yang membutuhkan argumentasi solutif dan inovatif dalam pembentukan norma baru pada transaksi kehidupan modern.Keyword: Implementasi; Maqashid Syari’ah; Ekonomi Islam